Validity and Reliability of Sport Organizational Citizenship Behavior Questionnaire - Hamid Sarani; Ali Mohammad Safania (The Society of Aging and Physical Activity (SAPA), 2014)
This research has been designed and conducted to evaluate the validity and reliability of organizational citizenship behavior questionnaire as an instrument in sports environment to assess the status of organizational citizenship behavior dimensions among the athletes of clubs. A 20-question questionnaire has been designed to measure the dimensions of organizational citizenship behavior by studying the background of existing researches and questionnaires. The statistical sample included all of male athletes working in Iran's Futsal premier league, and 144 questionnaires returned at last. In this research, the exploratory and confirmatory factor analysis was used to evaluate the validity of structure after assessing the validity of content and convergent validity (average variance extracted). And, to evaluate the combinational reliability, Cronbach's Alpha was used. Moreover, the applications SPSS and PLS-Graph were used to analyze data. The results of exploratory factor analysis indicated that five factors were explained by 69.10% of variance, and Kaiser-Meyer-Olkin was measured 85.5%. The reliability of the questionnaire was reported to be 91% and 93% based on Cronbach's Alpha and combinational reliability, respectively. Given the fact that the validity and reliability indexes of questionnaire have all been reported to be in a satisfactory condition, this questionnaire can be used as a valid and reliable questionnaire to measure organizational citizenship behavior and its dimensions.